Exiled intellectuals in Guatemala. The foundation of the Faculty of Humanities - Diaz Egurbide, Jon (CIAN-Revista de Historia de las Universidades, 2025)
This article explores the founding of the Faculty of Humanities at the University of San Carlos, which occurred during the Democratic Revolution in 1944. This period saw a significant influx of intellectuals and educators, primarily from Europe and Latin America, who were fleeing political conflicts such as the Spanish Civil War. Supported by Guatemala’s policies under President Juan José Arévalo, these scholars, including figures like María Solá de Sellarès, Pedro Bosch Gimpera, and Salvador Aguado Andreut. The Faculty benefited from foreign talent, consolidating itself as an academic and cultural development centre. The article outlines how these exiled academics contributed to fields like philosophy, history, arts and pedagogy, and how their presence catalyzed cultural and educational progress. It further reviews the initial curriculum and the challenges the Faculty faced in its formative years, as well as the structural changes that influenced the growth of higher education and humanistic studies in Guatemala.